Increased serial levels of platelet‐derived growth factor using hypoxic mesenchymal stem cell‐conditioned medium to promote closure acceler‐ ation in a full‐thickness wound - Pangesti Drawina; Taufiqurrachman Nasihun; Yan Wisnu Prajoko; Bayu Tirta Dirja; Nur Dina Amalina; Agung Putra (Universitas Gadjah Mada, 2022)
The healing process of a full‐thickness wound involves a complex cascade of cellular responses to reverse skin integrity formation. These processes require growth factors, particularly platelet‐derived growth factor (PDGF). Conversely, hypoxic mesenchymal stem‐cell‐conditioned medium (HMSC‐CM)‐contained growth factors notably contribute to acceleration of wound healing. This study aims to investigate the role of HMSC‐CM in controlling the serial levels of PDGF associated with accelerated wound closure in full‐thickness wounds. Twenty male Wistar rats with full‐thickness wounds were developed as animal models. The animals were randomly assigned to four groups, comprising two treatment groups (treated using HMSC‐CM at a high dose as P1 and at a low dose as P2), a control group (administration of base gel), and sham group (healthy group). PDGF levels were examined using an enzyme‐linked immunosorbent assay. Using ImageJ software, wound closure percentages were determined photographically. The study showed that there was a significant increase in PDGF levels on days 3 and 6 after HMSC‐CM treatment, followed by a decrease in PDGF levels on day 9. In line with these findings, wound closure percentage also increased significantly on days 6 and 9. In the rat model, HMSC‐CM administration may promote acceleration of wound closure by increasing serial PDGF levels in the full‐thickness wound.